Social Media Convergence in Islamic Organisations: Transforming Religious Communication in Persis, Muhammadiyah, and Nahdlatul Ulama in West Jawa - Sekar Arum Mandalia; Mohammad Zainul (International Journal of Nusantara Islam, 2026)
This study investigates the impact of social media convergence on the communication strategies of Islamic organizations in West Java, namely Persatuan Islam, Muhammadiyah and Nahdlatul Ulama. Using a qualitative approach, the research involved field observations, in-depth interviews, and content analyses of social media platforms such as YouTube, Instagram, and Facebook. Data were analyzed thematically to understand shifts in communication patterns and identity construction. The findings reveal that these organizations have actively adopted digital platforms to disseminate religious narratives, engage audiences, and construct institutional identities. Social media convergence enables decentralized communication, reshaping traditional religious authority and expanding outreach to digitally native demographics. NU and Muhammadiyah emphasize moderate and inclusive Islamic narratives, whereas Persis adopts a more doctrinal yet adaptive approach. All three demonstrate differentiated audience-targeting and platform strategies aligned with organizational values. This transformation reflects a structural shift in religious communication from hierarchical models to dialogic, participatory, and algorithm-aware strategies. Organizational success depends on media literacy, narrative adaptability, and collaborative leadership that integrates traditional and digital actors.